Unbundling the Voting Rights and Profit Claims of Common Shares - Blair, Douglas H.; Golbe, Devra L.; Gerard, James M. (Journal of Political Economy, 1989)
We analyze a model of a hostile takeover attempt in which shareholders are free to sell common-share voting rights as well as the shares themselves. Without taxation, only welfare-improving take-overs succeed. Allowing vote sales has no effect on the success of attempted takeovers or the profits of incumbent management or raiders. When taxes are levied, however, an inefficiently small number of value-increasing takeovers succeed if vote sales are prohibited. Allowing vote sales facilitates such takeovers and raises welfare. With taxation, incumbents would never prefer to defend against take-overs by purchasing votes, but raiders might well prefer this method.